Optimising the Use of Cemented Backfill by Using an Effective Stress Constitutive Model - Fourie, A.; Helinski, M.; Fahey, M. (Deep Mining 2007: Proceedings of the Fourth International Seminar on Deep and High Stress Mining, 2007)
Cemented backfill is an important contribution to ground support, particularly in high stress conditions. The rate at which strength, and more importantly stiffness, increases with time after placement of backfill is crucial to the safe and reliable use of this technology, but is an area that is currently poorly understood. The importance of the interaction between fill type, binder and water used during the hydration process and their impact on the rate of gain of stiffness and strength is highlighted. The principle of effective stress is critical to understanding how pore pressures generated during placement and consolidation of backfill affects the loads on barricades used to retain the newly-placed fill. Based on laboratory and in-situ experimental work, a constitutive model has recently been developed at the University of Western Australia that considers strength and stiffness gain with hydration time, self-desiccation and the effect on pore pressures in the fill. A comparison of pore pressures developed during the staged filling of a stope is used to illustrate the versatility of the model when incorporated into a finite element package. The utilisation of this model enables the choice of fill and binder combination to be optimised, and provides greater certainty in the use of cemented backfill in high stress conditions.